Greater intake of the MEDI diet is associated with better cognitive trajectory in older adults with type 2 diabetes. (August 2022) - Lotan, Roni; Ravona-Springer, Ramit; Shakked, Jacob; Lin, Hung-Mo; Ouyang, Yuxia; Shahar, Danit R.; Bezalel, Sharon; Agarwal, Puja; Dhana, Klodian; Heymann, Anthony; Sano, Mary; Schnaider Beeri, Michal
Abstract: Aims: To determine associations of three dietary patterns (Mediterranean (MEDI) diet, the Dietary Approaches to Stop Hypertension (DASH) diet and the Mediterranean- DASH Intervention for Neurodegenerative Delay (MIND) diet) with cognitive decline in older adults with type 2 diabetes mellitus (T2D). Methods: This is a longitudinal observational study. Participants (N = 960) from the Israel Diabetes and Cognitive Decline (IDCD) study were included in this study. A multivariable-adjusted model including all three dietary patterns concurrently was developed to investigate their independent effect on cognitive decline. Results: The mean follow up was 4.1 ± 2.1 years. While high adherence to both the MIND and the MEDI diet was associated with a slower decline, in the multivariable model only the associations of higher MEDI diet intake with greater decline in global cognition and in executive functions remained significant (β = 0.013, SE = 0.006; P = 0.042; β = 0.001, SE = 0.008, Pv = 0.023 respectively). Conclusions: In older adults with T2D, adherence to the MEDI is related to better cognitive trajectory. Diet is a meaningful factor in the path linking T2D and cognition.